2017
DOI: 10.11646/zootaxa.4250.4.1
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic status of two Telmatobius frog species (Anura: Telmatobiidae) from the western Andean slopes of northernmost Chile

Abstract: On the basis of molecular and morphological evidence, we evaluated the taxonomic identity of two species of Andean frogs of the genus Telmatobius: Telmatobius pefauri and T. zapahuirensis, present in the western Andean slopes at the northern extreme of Chile. We also investigated the taxonomic assignment of five populations of Telmatobius recently discovered around the type localities of these two species. The results indicate that T. pefauri inhabits, not only Murmuntani its type locality, but also the montan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 904 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…Cuevas et al (2020) that include specimens of a population of Telmatobius sp. of the Carcote Salt Flat (Sáez et al 2014;Fibla et al 2017Fibla et al , 2018, but none of them specify the coordinates or a precise site within the salt flat. Only in , the presence of a population of Telmatobius sp.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Cuevas et al (2020) that include specimens of a population of Telmatobius sp. of the Carcote Salt Flat (Sáez et al 2014;Fibla et al 2017Fibla et al , 2018, but none of them specify the coordinates or a precise site within the salt flat. Only in , the presence of a population of Telmatobius sp.…”
Section: Study Areamentioning
confidence: 99%
“…philippii by Lobos et al (2018). According to the molecular phylogenetic analysis of Sáez et al (2014), the only one where all of these populations were included, they are nested in different cladesthe T. pefauri (former T. zapahuirensis, see Fibla et al 2017) and T. hintoni species groups (not recovered in the most recent analysis by Barrionuevo 2017)respectively, so they clearly do not correspond to the same taxon. Nevertheless, the opposing hypotheses of and Cuevas et al (2020) were refuted by Correa (2021), who demonstrated, also using bibliographic sources, that the frog was first found near a warm swimming pool in Miño, a location at the source of Loa River, at the western foot of Miño Volcano (Fig.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hind‐limb relative length varies considerably in Telmatobius (Trueb, 1979; Vellard, 1951). Therefore, this character has been widely used in taxonomic studies (Barbour & Noble, 1920; Boulenger, 1882; Catenazzi, García, & Lehr, 2015; Cei, 1977; Cuevas & Formas, 2002; Fibla et al, 2017; Formas et al, 1999; Formas, Benavides, & Cuevas, 2003; Formas, Cuevas, & Nuñez, 2006; Noble, 1938; Parker, 1940; Trueb, 1979; Veloso & Trueb, 1976). In some cases, differences in the relative lengths of the hind limbs have been correlated with ecological factors.…”
Section: Introductionmentioning
confidence: 99%